2023
DOI: 10.7759/cureus.37648
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Reliability Analysis of YouTube Videos on Magnetic Resonance Imaging Claustrophobia

Abstract: Magnetic resonance imaging (MRI)-induced anxiety is not infrequent with a reported incidence as high as 37% and the rate of failed MRI imaging due to claustrophobia ranges between 0.5% and 14.5%. The objective of this study was to evaluate the quality and reliability of YouTube TM videos on MRI claustrophobia. MethodsSixty-five videos were included in the final analysis. Video information analyzed included video length (minutes), video content, qualification of the video uploaders, time of upload, time since u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…YouTube TM content analysis, the duration varies according to the research subject. However, in a study on claustrophobia, the mean video duration was 4.4 minutes [5]; in a study on infertility, it was 8.1 minutes [16]; and in a study on autism, it was 8.53 minutes [17]. The longer mean video durations in our study may be related to the need for a more detailed explanation of specific psychiatric conditions.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…YouTube TM content analysis, the duration varies according to the research subject. However, in a study on claustrophobia, the mean video duration was 4.4 minutes [5]; in a study on infertility, it was 8.1 minutes [16]; and in a study on autism, it was 8.53 minutes [17]. The longer mean video durations in our study may be related to the need for a more detailed explanation of specific psychiatric conditions.…”
Section: Discussioncontrasting
confidence: 63%
“…However, it has been observed that a substantial rate of 26% was uploaded by non-professionals. Although it varies according to the field studied in the literature, it has been observed that the rate of professional videos and non-professional videos is high in some studies [5,14,22]. Different results between studies may be due to the prevalence, recognition rate, or characteristics of the diseases in the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations